-50+9x=16+6x

Simple and best practice solution for -50+9x=16+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -50+9x=16+6x equation:


Simplifying
-50 + 9x = 16 + 6x

Solving
-50 + 9x = 16 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-50 + 9x + -6x = 16 + 6x + -6x

Combine like terms: 9x + -6x = 3x
-50 + 3x = 16 + 6x + -6x

Combine like terms: 6x + -6x = 0
-50 + 3x = 16 + 0
-50 + 3x = 16

Add '50' to each side of the equation.
-50 + 50 + 3x = 16 + 50

Combine like terms: -50 + 50 = 0
0 + 3x = 16 + 50
3x = 16 + 50

Combine like terms: 16 + 50 = 66
3x = 66

Divide each side by '3'.
x = 22

Simplifying
x = 22

See similar equations:

| f(x)=-0.75x-1 | | 6x+y-4+x-9y+1=180 | | 5w+1=3w-3 | | m(x)=-6.5x | | 5b+1=2(b+2) | | x-48=28-3x | | 5x+5+5=14+2x | | h(x)=2.25x | | 37x+12y=22 | | (.5)(6)(x)=27 | | -35-7x=23-9x | | -95+2x=118-6x | | 3+5+x=10 | | -95+2x=-9x+37 | | 5x-3=6x+14x | | a-3=5-s | | 47q-2=61q-86 | | 9k=-300 | | -28-5x=22-7x | | -4x+8+6x=2 | | x-(4x-12)=18 | | z^10-2*z^5+2=0 | | (6x-5)(6x-7)=0 | | x=loge^2 | | 12y-12x-(-13y-65x)= | | 4100=4000n-500 | | -113+5x=118-6x | | 12-m=5m-6 | | 5.6=2.3+3z | | 0=-16x^2+24x+160 | | 2.5x+.45=.95 | | ab-5ab+15ab= |

Equations solver categories